PERFORMANCE ANALYSIS OF THE EU MEMBER STATES' TAX SYSTEMS - Mariana-Luminita COMAN (LINTA) (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The topic of the tax system efficiency is in the area of research interest. Economists-practitioners and government officials are also interested in this issue. Today, more than ever, everyone is looking for solutions to increase tax revenue collection in order to cover current public spending, to provide quality public goods and services to citizens and to stimulate economic development. The design of a tax system influences investors' decisions, it can create incentives for investment and consumption or it can generate implications for negative externalities. The efficiency of a tax system is evaluated in terms of the high degree of tax revenue collection, in terms of low costs for taxpayers and the tax administration. The paper examines conceptual and factual aspects of the EU Member States' tax systems. The paper highlights particularities of EU Member States' tax systems. Decision makers must take into account these particularities in adapting the analytical framework for evaluating the tax administration performance. The performance analysis of EU Member States' tax systems offers the possibility to identify some tools for evaluating the Romanian tax administration performance in order to recover the gaps compared to other countries.